Biologically induced alternative states in two rocky subtidal benthic communities - Barkai, Amos (Department of Biological Sciences, 2016)
This thesis is concerned with the contrasting communities that occur in the subtidal zones of two closely situated islands in Saldanha Bay on the west coast of South Africa: Both are guano islands, supporting substantial populations of seabirds. They have a similar bottom topography and experience similar physical conditions. Despite these similarities their subtidal benthic communities are however, radically different. Marcus Island has prolific beds of the black mussel Choromytilus meridionalis, accompanied by a large number of other species, notably the sea urchin Parechinus angulosus, the holothurians Pentacta doliolum, Thyone aurea and Trachythyone insolens, large population of whelks, mostly Burnupena spp. and the barnacles Austromegabalanus cylindricus and Notomegabalanus algicola. In contrast, Malgas Island is dominated by a large population of the rock lobster Jasus lalandii together with a dense seaweed flora, and has small numbers of the ribbed mussel Aulacomya ater and the whelks Argobuccinum pustulosum and Burnupena papyracea.